PENGATURAN BLUE BOND SEBAGAI INSTRUMEN PEMBIAYAAN BERKELANJUTAN DI INDONESIA - Luthfia, Sahira Sajjadia (Penerbit Universitas Atma Jaya Yogyakarta, 2026)
This research explores the legal aspects of blue bond regulation as a complementary tool for private-sector financing through public-private partnerships. With increasing investor and public interest in sustainability, Indonesia's regulatory framework must be precise and adhere to both national and international sustainability standards. The study examines the relationship between legislation governing Blue Bonds and their effectiveness in promoting sustainable development within the Indonesian capital market. Using a juridical-normative approach, this research analyzes legal doctrines and regulations. Research findings indicate that blue bonds hold significant potential as a sustainable financing instrument through structured mechanisms for fund utilization, project selection, management, and reporting. However, this potential has not yet been fully realized due to the lack of specific regulations that comprehensively accommodate the characteristics of marine projects.